Inheritance of blood potassium and Hemoglobin types in Naemi sheep and their relation with some productive characters (مجلة ديالى للبحوث الانسانية, 2022)
Some 36 Naemi ewes , 4 rams were typed for blood potassium and hemoglobin , and 19 offspring were typed for blood potassium . HK (High potassium) gene frequencies for ewes, rams and lambs were of the order of 0.87, 0.87 and 0.89 respectively , for the HbB gene the frequency for sheep was 0.97 . HK sheep had a significantly higher in birth weight and body weight (p